Academic Senate Minutes 2004-09-02 - Academic Senate:::::::::
Chair Report. Agenda – Approved. Minutes of 4/30/2020 – Approved. Consent items: Curriculum revision for Dance elevation to a Major; Curriculum revision to the Educational Leadership Program Administrative Service Credential and Curriculum revisions to the BA in Spanish and French – Approved. President Report. Provost Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President for Student Affairs Report. Associated Students Report. Statewide Senators Report. Staff Representative Report. Election of At-Large Members to Ex Com for AY 20-21 – Amal Munayer, Sam Brannen. From FSAC: Policy revision: RTP policy G. Levels and Sequence of RTP Review #2 and #3 – Second Reading – Approved. Internship Policy – Second Reading – Approved. From APARC: Priority Recommendations for AY 20-21 – Second Reading – Approved. APARC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Resolution on the Matter of Laura Alice Watt – approved by acclaim. Changing of the Guard.